Formaldehyde Sensor With Enhanced Performance Using Microsphere Resonator-Coupled ZnO Nanorods Coated Glass - Harun, Sulaiman Wadi; Yasin, M.; Md Johari, Md Ashadi; Johari, Siti Halma; Jali, Mohd Hafiz; Abdul Rahim, Hazli Rafis; Mohamad Ali, Ummu Umairah; Mohamed, Habibah (Elsevier Ltd, 2021)
An enhanced formaldehyde (CH2O) sensor incorporating microsphere resonator and zinc oxide (ZnO) nanorods coated glass is reported. The microsphere resonator with a diameter of 234 µm and the ZnO nanorods coated glass surface was fabricated using the hydrothermal synthesis method for 12 h. A significant response to formaldehyde concentration levels ranging from 0 ppm to 0.18 ppm was observed. Sensitivity improves by a factor of 1.84 and 1.33 in terms of output power and wavelength shift, respectively, compared to straight microfiber laid on the ZnO coated glass substrate. It produces exceptionally good resolution with 0.0031 ppm as compared to its counterpart with 0.0058 ppm. The proposed formaldehyde sensor utilizes a high energy density behaviour of a microsphere resonator for evanescent field coupling with the surrounding analyte. It also possesses a robust chemisorption process on the ZnO nanorods surface to enhance the sensitivity towards formaldehyde vapour. Besides improving performance, it exhibits a simple approach that reduced the complexity to handle the microfiber during the synthesis process. This proposed technique has shown excellent experiment results for formaldehyde sensing applications.